PHONETIC STYLISTICS - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Stylistics is (Greek: stylos - writing, writing stick). means, stylistic methodology is a study of language styles of linguistics, which studies the essence and peculiarities of the functional folding of the language from the point of view of synchrony and diachrony at the lexical-phraseological, phonetic, morphological, word formation and syntactic levels, the literary language in different linguistic situations, the variety of written literature - a network describing norms and methods of application in different types and genres, in different spheres of social life. In S., the semantic and expressive nuances of parallel synonymous language expressions, interrelated variants of linguistic units are studied. In such options, it was possible to choose the one necessary for a specific speech situation. Key words: Artistic speech, poetic speech, poetic speech, word formation, creative style, stylistics, linguistics, literary studies, language and speech, occasionalism, individualism.